2020
DOI: 10.1111/ajt.15592
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of donor-reactive T cell clones after human liver transplant

Abstract: | INTRODUC TI ONLiver transplantation has been associated with relatively high rates of successful immunosuppression withdrawal in recipients who have been free of rejection for years. 1,2 Despite T cell infiltration associated with hepatitis C virus (HCV) and recurrent HCV posttransplant, 3 a subset of HCV-infected liver transplant recipients have successfully achieved tolerance. 4Spontaneous liver allograft tolerance occurs in rodent models across major histocompatibility complex barriers 5 and is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…suggesting that T cell deletion is the most important mechanism mediating tolerance after mouse liver transplantation. It is also consistent with reports suggesting that both the hepatic parenchyma and PLs contribute to tolerance induction after rat LT (18) and that human liver transplantation is associated with deletion of T cells bearing specific TCR beta sequences (60). Tolerance to liver allografts is consistent with our studies showing that persisting high levels of intrahepatic antigen expression, a situation akin to that associated with organ transplantation, are generally associated with tolerance (29).…”
Section: Disruption Of T Cell Activation In Lymphoid Tissues By Plsupporting
confidence: 92%
“…suggesting that T cell deletion is the most important mechanism mediating tolerance after mouse liver transplantation. It is also consistent with reports suggesting that both the hepatic parenchyma and PLs contribute to tolerance induction after rat LT (18) and that human liver transplantation is associated with deletion of T cells bearing specific TCR beta sequences (60). Tolerance to liver allografts is consistent with our studies showing that persisting high levels of intrahepatic antigen expression, a situation akin to that associated with organ transplantation, are generally associated with tolerance (29).…”
Section: Disruption Of T Cell Activation In Lymphoid Tissues By Plsupporting
confidence: 92%
“…This would be in keeping with the lack of clinically apparent nonspecific immunosuppressive effects observed following Treg infusion. Alternatively, the infused Tregs could have amplified the well‐documented capacity of liver allografts to delete donor‐reactive T cell clones …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the infused Tregs could have amplified the well-documented capacity of liver allografts to delete donor-reactive T cell clones. 34,35 In summary, we have described here the successful expansion under GMP conditions of polyclonal Tregs isolated from both endstage liver disease patients awaiting liver transplantation and stable liver transplant recipients under maintenance immunosuppression.…”
Section: Nor-reactive Tregs and Chimeric Antigen Receptor (Car)-exprementioning
confidence: 99%
“…The Colombia group developed a TCR sequencing-based analysis of responding T cells in CFSE-MLR to identify and track a significant fraction of alloreactive T cell repertoire in any donor-recipient pair (105,106). They have shown that liver-induced clonal deletion detected by tracking alloreactive TCR clones in pre-transplant MLR may contribute to achieving tolerance in LT recipients (107). Furthermore, another potentially beneficial application of MLR is the detection of activating induced markers and cytokines.…”
Section: Immune Monitoring To Personalize Immunosuppression Toward Tomentioning
confidence: 99%